An Updated Water Masses Stratification of Indonesian Maritime Continent (IMC) Attributed to Normal and ENSO Conditions by Argo Float - Bahiyah, Amirotul; Wirasatriya, Anindya; Mardiansyah, Wijaya; Iskandar, Iskhaq (Science and Technology Indonesia, 2024)
The tropical area of the Indonesian Maritime Continent (IMC) is frequently regulated by El Niño Southern Oscillation (ENSO), resulting in various water mass stratification in every climate event, such as El Niño and La Niña occurrences. As a consequence, changes in the typical Indonesian Throughflow (ITF) are linked to ENSO circumstances that affect the Indian Ocean. This study used Argo float data to evaluate the change in water mass stratification and vertical density profiles along the main pathway of ITF at each event. However, due to a scarcity of observation data, the comparison study of normal to ENSO occurrences has been limited in the ITF area. In typical circumstances throughout the year, the entrance channel (the western Pacific Ocean, the northern waters of Molucca Island, and the Halmahera Sea) had a higher saline value and cooler water masses than other ITF channels, with a range of roughly 33.5 - 35.5 PSU/13 - 22 ◦C, particularly during the Northwest (NW) Monsoon (December to February or DJF). Unlike the inlet, the Temperature-Salinity (T-S) diagram showed a declining value in both parameters (Celebes Sea, Makassar Strait, and Molucca Sea). Still, the outflow pathway in the Southeastern Tropical Indian Ocean (SETIO) showed a rising T-S diagram. During La Niña events, IMC water masses are often portrayed as fresher and warmer, while reverse circumstances are depicted in El Niño events with exclusion at SETIO station, indicating saltier and colder water masses than normal conditions. An extreme alteration with a large T-S range is mostly depicted in Makassar Strait from Southeast (SE) monsoon (September to November or SON) to NW monsoon, followed by the Banda Sea and then the Molucca Sea.